Effect of urethral meatus cleansing on midstream urine contamination rate in boys - Musim Musim; M P Damanik; Purnomo Suryantoro (Paediatrica Indonesiana, 2008)
Background Clean-catch midstream urine (MSU) remains thestandard procedure for urine collection even if it's role to reducebacterial contamination rate is unclear.Objective To compare bacterial contamination rate betweenclean-catch (cleaning urethral meatus with medicated soap) andnon clean-catch MSU among boys.Methods An experimental study with parallel groups and blockrandomization was conducted. Toilet-trained boys aged 3 to 18years, without symptoms or signs of urinary tract infection wererecruited from the Pediatric Outpatient Clinic at Sardjito Hospitaland from a local elementary school. Subjects with history of renaldisease, those who were on under antibiotic treatment in thepreceding week, or with meatal abnormality or non-cooperativewere excluded. Urine specimen was collected by a trained nurse,and was cultured within one hour by personnel blinded to theassignment. Significant bacteriuria was defined as growth of asingle pathogenic organism (degree of pathogenicity group I-III)with colony count 2: 105 colony forming unit/mi. Contaminationwas defined as any growth not fulfilling criteria for significantbacteriuria or growth of multiple organisms.Results A total of 80 boys were enrolled. The contamination ratein the clean-catch group was 13% (5 out of 40) compared with10% (4 out of 40) in the non clean-catch group (P=l.O). Theadjusted risk ratio for contamination in the clean-catch MSUgroup, adjusted to age and circumcision status, was 1.37 (95%CI 0.42; 4.51).Conclusion Clean-catch method does not reduce bacterial con-tamination rate of midstream urine cultures in boys